# Difference of sine of compound angles to Product form Transformation

## Formula

$\large \sin (a+b) -\sin (a-b) =$ $\large 2.\cos a .\sin b$

### Proof

Two angles can form compound angles in sum and difference form. The subtraction of sines of them can be transformed as the product of cosine and sine of angles. It is called the sum to product form transformation rule as per trigonometry.

###### Step: 1

Assume, $a$ and $b$ are two angles and the compound angles of them are $a+b$ and $a-b$. The expansion of sine of sum and difference of the angles are written trigonometrically as follows.

$(1). \,\,\,\,\,\,$ $\sin(a+b)$ $=$ $\sin a . \cos b$ $+$ $\cos a . \sin b$

$(2). \,\,\,\,\,\,$ $\sin(a-b)$ $=$ $\sin a . \cos b$ $-$ $\cos a . \sin b$

###### Step: 2

Subtract the expansion of the sine of difference of the angles from the expansion of the sine of sum of the angles.

$\implies \sin(a+b) -\sin(a-b)$ $=$ $(\sin a . \cos b$ $+$ $\cos a . \sin b)$ $-$ $(\sin a . \cos b$ $-$ $\cos a . \sin b)$

$\implies \sin(a+b) -\sin(a-b)$ $=$ $\sin a . \cos b$ $+$ $\cos a . \sin b$ $-$ $\sin a . \cos b$ $+$ $\cos a . \sin b$

$\implies \sin(a+b) -\sin(a-b)$ $=$ $\sin a . \cos b$ $-$ $\sin a . \cos b$ $+$ $\cos a . \sin b$ $+$ $\cos a . \sin b$

$\implies \sin(a+b) -\sin(a-b)$ $=$ $\require{cancel} \cancel{\sin a . \cos b}$ $-$ $\require{cancel} \cancel{\sin a . \cos b}$ $+$ $\cos a . \sin b$ $+$ $\cos a . \sin b$

$\therefore \,\,\,\,\,\, \sin(a+b) -\sin(a-b)$ $=$ $2 \cos a . \sin b$

It is successfully transformed that the difference of sine of difference of two angles and sine of sum of two angles is equal to twice the product of sine of first angle and cosine of second angle.

#### Verification

Assume $a = 60^\circ$ and $b = 30^\circ$. Substitute these two angles in both sides of the equation and then compare the result.

###### Step: 1

$\sin(a+b) -\sin(a-b)$ $=$ $\sin(60^\circ+30^\circ) -\sin(60^\circ-30^\circ)$

$\implies \sin(60^\circ+30^\circ) -\sin(60^\circ-30^\circ)$ $=$ $\sin(90^\circ) -\sin(30^\circ)$

$\implies \sin(60^\circ+30^\circ) -\sin(60^\circ-30^\circ)$ $=$ $1-\dfrac{1}{2}$

$\therefore \,\,\,\,\,\, \sin(60^\circ+30^\circ) -\sin(60^\circ-30^\circ)$ $=$ $\dfrac{1}{2}$

###### Step: 2

$2 \cos a . \sin b = 2 \times \cos(60^\circ) \times \sin(30^\circ)$

$\implies 2 \times \cos(60^\circ) \times \sin(30^\circ)$ $=$ $2 \times \dfrac{1}{2} \times \dfrac{1}{2}$

$\implies 2 \times \cos(60^\circ) \times \sin(30^\circ)$ $=$ $2 \times {\Bigg(\dfrac{1}{2}\Bigg)}^2$

$\implies 2 \times \cos(60^\circ) \times \sin(30^\circ)$ $=$ $2 \times \dfrac{1}{4}$

$\therefore \,\,\,\,\,\, 2 \times \cos(60^\circ) \times \sin(30^\circ)$ $=$ $\dfrac{1}{2}$

###### Step: 3

Now compare both results to understand the relation between them.

$\therefore \,\,\,\,\,\, \sin(60^\circ+30^\circ) + \sin(60^\circ-30^\circ)$ $=$ $2 \times \cos(60^\circ) \times \sin(30^\circ)$ $=$ $\dfrac{1}{2}$

###### Other forms

The sum to product form transformation law can also be written in other form.

$\large \sin (x+y) -\sin (x-y) =$ $\large 2.\cos x .\sin y$

$\large \sin (\alpha+\beta) -\sin (\alpha-\beta) =$ $\large 2.\cos \alpha .\sin \beta$

###### General form

$\sin (sum \, of \, two \, angles)$ $-$ $\sin (difference \, of \, two \, angles)$ $=$ $2$ $\times$ $\cos \, of \, first \, angle$ $\times$ $\sin of \, second \, angle$

Latest Math Topics
Latest Math Problems
Email subscription
Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers. Know more
Follow us on Social Media
###### Math Problems

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.

Learn more